2019
DOI: 10.21037/gs.2019.07.01
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound imaging classifications of thyroid nodules for malignancy risk stratification and clinical management: state of the art

Abstract: Assessing the risk of malignancy in the thyroid with ultrasound (US) is crucial in patients with nodules, as it can aid in selecting those who should have a fine-needle aspiration (FNA) biopsy performed. Many studies have examined whether the US characteristics of thyroid nodules are useful indicators of histological malignancy. Overall, these investigations have identified a few US features that are significantly more frequent in malignant thyroid nodules which can be coalesced into a defining set to be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 38 publications
(33 reference statements)
1
32
0
6
Order By: Relevance
“…It is important to note that there are certain differences among the different TIRADS systems (such as ACR and EU TIRADS) compared to the presently applied K-TIRADS; for a comparison of these systems, see the review by Chiara et al [59].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that there are certain differences among the different TIRADS systems (such as ACR and EU TIRADS) compared to the presently applied K-TIRADS; for a comparison of these systems, see the review by Chiara et al [59].…”
Section: Discussionmentioning
confidence: 99%
“…Then this author performed a scoping review of the peer‐reviewed literature in electronic databases (e‐databases) to rapidly identify articles comparing two or more UGMTNs and/or non‐UGMTNs . E‐databases included Medline (PubMed), EBSCO, Google, and Google Scholar published from 2010 to 2019 to capture articles comparing UGMTNs or non‐UGMTNs . The keyword combinations of thyroid, nodule, ultrasound, risk, comparison, guideline, malignancy, and classification returned 28 peer‐reviewed articles comparing two or more UGMTNs.…”
Section: Does a Plethora Of Ugmtns Exist?mentioning
confidence: 99%
“…Their subanalysis of TR3 and TR4 grades revealed that the ACR TI‐RADS‐17 recommendations for discriminating nodules with high‐risk cytology might miss a small percentage of cancers. A third 2019 study by Floridi et al reviewed and compared the ACR TI‐RADS‐2017, EU TI‐RADS, South Korean TI‐RADS, AACE/ACE/AME classification, ATA‐2015, and BTA UGMTNs . Although all UGMTNs achieved high sensitivities and specificities, the authors could not establish a “best” system due to their study limitations.…”
Section: Does a Plethora Of Ugmtns Exist?mentioning
confidence: 99%
“…Severino Rey Nodar 1 , Ignacio Torrero De Pedro 2 1 Departamento de Anatomía Patológica Hospital Manises, Valencia, España. 2 Alumno de Escuela de Medicina de la Universidad CEU Cardenal Herrera Valencia.…”
Section: -Patología Molecular Del Cáncer De Tiroides Revisión De Aunclassified